Analysis of Factors Influencing Farmers’ Responses toward the Adoption of Hand Tractors in Palae Village, Sinjai Regency - Hasrini; Megawati; Fadilah Nurdin (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
This study aims to analyze the factors influencing rice farmers’ responses toward the adoption of hand tractors in Palae Village, Sinjai Regency. The research employed a quantitative descriptive method using multiple linear regression analysis. The study population consisted of 772 farmers, with the sample determined using the Slovin formula. The results showed that, simultaneously, all independent variables significantly affected farmers’ responses. Partially, the variables of age, education level, and farming experience had a negative and significant effect, while land area and time efficiency had a positive and significant effect on farmers’ responses. Meanwhile, operational costs were found to have no significant effect. These findings indicate that practical benefits, such as time savings and ease of land cultivation, are the main driving factors behind farmers’ positive responses toward agricultural mechanization in the research area.